IMPLEMENTASI MANAJEMEN DAN AUTENTIKASI PENGGUNA HOTSPOT MENGGUNAKAN MIKROTIK HOTSPOT MANAGEMENT MIKHMON DI KEDAI KOPI LEGALITA - Adi Wibowo; Bambang Triraharjo (LPPM Universitas Muhammadiyah Kotabumi, 2023)
Abstract: Internet access is a major requirement for individuals and businesses, including coffee shops in today's digital era, MikroTik Hotspot provides features such as user authentication, bandwidth management, access restrictions, and internet usage monitoring. This study aims to evaluate the effectiveness and efficiency of hotspot user authentication and management systems and to provide recommendations for improved performance and better usage. Proper implementation can improve the quality of internet services, customer satisfaction, and coffee shop operational productivity. In addition, this article also has the potential to improve network security and privacy protection. This research provides insights for the coffee shop industry in managing hotspot internet access and can be the best example in hotspot management practices. In the long term, this implementation can provide a competitive advantage, attract new customers, increase customer loyalty, and strengthen the business reputation of Legalita coffee shops. The research was conducted using the NDLC (Network Development Life Cycle) method. The conclusions of the research conducted are Effectiveness of Hotspot Management, Ease of Use and Administration, Secure User Authentication, Comprehensive Monitoring and Reporting, Satisfying User Experience